Soliton solution and conservation laws of the Zakharov equation in plasmas with power law nonlinearity - Morris, Richard; Kara, Abdul Hamid Hamid; Biswas, Anjan (Nonlinear Analysis: Modelling and Control, 2013)
This paper studies the Zakharov equation with power law nonlinearity. The traveling wave hypothesis is applied to obtain the 1-soliton solution of this equation. The multiplier method from Lie symmetries is subsequently utilized to obtain the conservation laws of the equations. Finally, using the exact 1-soliton solution, the conserved quantities are listed.